Cerebral blood flow in the paracentral lobule is associated with poor subjective sleep quality among patients with a history of methadone maintenance treatment - Sun, Jiaxue; Lu, Yi; Kong, Deshenyue; Lin, Wenhua; Du, Jinze; Wang, Guangqing; Ma, Xingfeng; Li, Congbin; Wang, Kunhua; Zhu, Mei; Xu, Yu (Frontiers in Neurology, 2024)
Introduction: Sleep disorders are prevalent and significant among individuals receiving methadone maintenance treatment (MMT), leading to a detrimental impact on their quality of life and treatment adherence. Cerebral blood flow (CBF) plays a crucial role in the development of various diseases ; however, but its' relationship with sleep disorders remains uncertain. This observational study focuses on possible correlations between CBF and poor subjective sleep quality in methadone maintenance treatment (MMT)patients.Methods: A total of 75 participants with a history of MMT were recruited and assessed with pseudocontinuous arterial spin labeling magnetic resonance imaging. CBF was ascertained using pseudocontinuous arterial spin labeling magnetic resonance imaging. LAASO regression model were conducted to pick out the Region-of-interest (ROI) most associated with sleep disturbance. The sleep quality 删除: in 删除: ndergoing 删除: onset and progression of numerous diseases 删除: the association between CBF and 删除: To understanding the neurobiological mechanisms linkingof sleep disturbance in methadone maintenance treatment (MMT) MMT patients.